PEMANFAATAN LIMBAH IKAN SIDAT INDONESIA (Anguilla bicolor) SEBAGAI TEPUNG PADA INDUSTRI PENGOLAHAN IKAN DI PALABUHANRATU, KABUPATEN SUKABUMI - RA Hangesti Emi Widyasari; Clara M Kusharto; Budy Wiryawan; Eko Sri Wiyono; Sugeng Heri Suseno (Jurnal Gizi dan Pangan, 2013)
This research aims to analyze the nutritive value of flour head, liver powder and bone meal as by product of Indonesian eel (Anguilla bicolor) processing. Eel waste flour was made by using a thermal process in the drum dryer fish flouring mill PT. Carmelitha Lestari in Bogor, whereas proximate analysis for chemical tests were performed in the laboratory of Integrated Chemical Laboratory, IPB and direct observation was conducted in PT Jawa Suisan Indah, Palabuhanratu Sukabumi district in October 2012—April 2013. The nutritive value based on proximate analysis showed that head flour, liver flour, and bone flour contained protein 61.78%, 53.92%, and 41.01%; fat 15.55%, 27.28%, 13.07%; carbohydrate 11.48%; 14.96%, 8.13%; water 5.44%, 8.48%, 3.01%; ash 12.95%, 3.62%, 37.49%, and crude fiber 1.33%, 0.04%, 1.11%, respectively.